Expression of voltage-dependent potassium channels in first trimester human placentae - Mistry, Hiten D.; Kurlak, L.O.; Whitley, Guy S.; Cartwright, Judith E.; Broughton Pipkin, Fiona; Tribe, Rachel M. (Elsevier, 2014)
Potassium channel α-subunits encoded by KCNQ1-5 genes form voltage-dependent channels (Kv7), modulated by KCNE1-5 encoded accessory proteins. The aim was to determine KCNQ and KCNE mRNA expression and assess protein expression/localisation of the KCNQ3 and KCNE5 isoforms in first trimester placental tissue. Placentae were obtained from women undergoing elective surgical termination of pregnancy (TOP) at <10 weeks’ (early TOP) and >10 weeks’ (mid TOP) gestations. KCNQ1-5 expression was unchanged during the first trimester. KCNE5 expression increased in mid TOP vs. early TOP samples (P=0.022). This novel study reports mRNA and protein expression of Kv7 channels in first trimester placentae.